Silence, like breathing - Van der Nest, Megan (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2012)
In this collection of free verse lyric poems I have drawn inspiration from childhood memories, as well as from the natural world and encounters with the people around me. Each poem focuses on a small moment, presenting an emotive portrait of a memory or an experience. These small moments lead, cumulatively, to deeper insights into myself and the world around me. The collection is divided into four seasons, in part because the work is strongly influenced by the natural world, but also because the progression of the seasons mirrors something of the personal journey reflected in the poems.
Writing portfolio
Keywords: South African poetry (English) -- 21st century; Creative writing (Higher education); Diaries -- Authorship; English language -- Writing